Expression of Survivin and Cortactin in Colorectal Adenocarcinoma: Association with Clinicopathological Parameters. Issue 1 (3rd June 2013) - Lee, Ying-Yu; Yu, Cheng-Ping; Lin, Chih-Kung; Nieh, Shin; Hsu, Kuo-Feng; Chiang, Hung; Jin, Jong-Shiaw
Abstract : Objective : Survivin and cortactin are factors that promote tumor progression. We tested the hypothesis that survivin and cortactin expressions correlate with the clinico-pathological parameters of colorectal adenocarcinomas and survival time. Methods: Immunohistochemical analysis of survivin and cortactin were performed using tissue microarrays of 119 specimens from 18 well, 50 moderately, and 27 poorly differentiated colorectal adenocarcinomas and 24 colorectal adenomas with dysplasia. As control, 10 specimens of normal colorectal epithelia were included. Results : The percentage of cells immunostained and the immunostaining scores for survivin and cortactin were all significantly higher in well-, moderately, and poorly differentiated colorectal adenocarcinomas than in normal colorectal epithelia. The survivin immunostaining score was significantly correlated with T, M, and AJCC/TNM stages (p `0.05). For cortactin, the score was significantly correlated with T and M stages (p ` 0.05). Higher survivin immunostaining score was associated with higher mortality. Conclusions : Higher expression of survivin and cortactin correlates significantly with tumor stages and shorter survival time. Survivin and cortactin may be good biomarkers of aggressiveness of colorectal adenocarcinomas. Our findings require validation in independent cohorts and these data support the potential targeting of survivin and cortactin for the development of novel therapeutic strategies.